Evaluation of the Risk of Nitrofurantoin Lung Injury and Its Efficacy in Diminished Kidney Function in Older Adults in a Large Integrated Healthcare System: A Matched Cohort Study. Issue 4 (April 2016) - Santos, Jody M.; Batech, Michael; Pelter, Mitchell A.; Deamer, Robert L.
Abstract : Objectives: To determine the risk to older adults of lung injury associated with treatment of cystitis using nitrofurantoin and the risk of treatment failure in the presence of diminished creatinine clearance (CrCl). Design: Retrospective, matched cohort. Setting: Integrated healthcare system. Participants: Individuals aged 65 and older with a diagnosis of cystitis between 2007 and 2012 who were given nitrofurantoin (N = 13, 421) were matched 1:3 on age, sex, race and ethnicity, and prescription date with individuals who were given other antibiotics for cystitis. Measurements: Conditional logistic regression determined the association between nitrofurantoin and lung injury in the matched cohort. In participants exposed to nitrofurantoin, chronic treatment was compared with acute treatment using multivariable logistic regression. Treatment failure was compared in three CrCl groups. Results: Nitrofurantoin exposure was not statistically significantly associated with lung injury (adjusted risk ratio (aRR) = 0.90, 95% confidence interval (CI) = 0.80–1.00), but chronic nitrofurantoin therapy was associated with greater risk of lung injury than acute exposure (aRR = 1.53, 95% CI = 1.04, 2.24). Treatment failure rates did not differ according to CrCl. Conclusion: This large, retrospective, matched‐cohort study conducted in older adults supports the 2012 American Geriatrics Society Updated Beers Criteria for Potentially Inappropriate Medication Use in Older Adults recommendations against the use nitrofurantoin for long‐term suppressive treatment of cystitis but not the recommendation against its use in poor renal function because of the risk of treatment failure.